Identification and High-performance Liquid Chromatography Quantification of Aflatoxins in Red Chili (Capsicum annuum L.) in Guntur, Andhra Pradesh, India - Sailaja, Ommi (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Aflatoxins are hepatogenic, teratogenic, immunosuppressive, and carcinogenic fungal metabolites found in feeds, nuts, wine-grapes, spices, and other grain crops. Humans are exposed to AFs through consumption of mycotoxin-contaminated foods. Aim: This study aimed to determine the prevalence of aflatoxin contamination in red chili samples collected at different locations in Guntur, Andhra Pradesh. Materials and Methods: Aflatoxins were extracted by liquid-liquid extraction method using chloroform solvent. The qualitative and quantitative analysis of aflatoxins present in the samples was analyzed using thin-layer chromatography and high-performance liquid chromatography techniques. Results and Discussions: Among the samples in the study, two samples S3 and S7 were not infected with aflatoxin producing fungi. In sample S5, aflatoxin G1, G2, and B2 were identified and G1 was found to be very high (21.32 ng/g). The high amount of aflatoxin B2 (34.02 ng/g) was observed in sample S2. Among the samples having aflatoxins, aflatoxin G2 was found in all the samples. Strict measures are necessary to produce high-quality red chilies. Red chili berry must be treated to reduce molds before the production of powders for consumption.